PKM Pelatihan Digitalisasi dan Pembukuan Komputerisasi Sederhana pada UMKM Raaf Mart Bassura City Jakarta Timur - Ria Susanti Johan; Widiyarini Widiyarini; Iin Asikin; Desy Septariani; Agus Supandi (Jurnal Ragam Pengabdian, 2025)
The rapid advancement of digital technology has created both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs), particularly in financial management and operational efficiency. However, many micro-scale MSMEs still rely on manual bookkeeping methods, resulting in poor financial transparency and difficulty in making strategic business decisions. This community engagement program aimed to empower RAAF Mart, an MSME located in Bassura City, East Jakarta, by providing training on digitalization and simple computerized bookkeeping using Microsoft Excel. The program was conducted through participatory methods, including needs assessment, hands-on workshops, and pre-test and post-test evaluations. The results showed a significant improvement in participants’ understanding of basic financial literacy and digital tools. Prior to the training, most participants lacked knowledge of cash flow tracking, income statement preparation, and the use of spreadsheet software. After the training, participants were able to implement a daily bookkeeping system using a customized Excel template. The training also fostered a positive shift in mindset toward the importance of separating personal and business finances. This program demonstrated that simple, contextualized digital training can be highly effective in supporting the digital transformation of MSMEs. Continued mentoring and follow-up support are recommended to ensure sustainable implementation.